2009
DOI: 10.1093/ndt/gfp200
|View full text |Cite
|
Sign up to set email alerts
|

Time of onset in haemodialysis access-induced distal ischaemia (HAIDI) is related to the access type

Abstract: Hand ischaemia occurring early after routine access surgery is usually related to grafts and not to autogenous access construction. If patients have several risk factors for acute hand ischaemia (diabetes), nephrologists and vascular surgeons may choose an autogenous AVA. A disadvantage of an autogenous access is its association with chronic hand ischaemia, particularly if constructed with a brachial artery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
80
3
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(90 citation statements)
references
References 39 publications
3
80
3
4
Order By: Relevance
“…Women, in the our research, have no higher risk for developing distal hypoperfusion, probably because they accounted for only one-third of our respondents. On the other hand, patients who had symptoms of distal ischemia were significantly older than those without this syndrome, which confirms old age as a factor that characterizes patients with DHIS [6,11] . Half of our respondents were smokers and this habit has been established as a significant feature in patients with pronounced symptoms of distal ischemia.…”
Section: Factors That Define Digital Hypoperfusion Ischemic Syndromementioning
confidence: 81%
See 1 more Smart Citation
“…Women, in the our research, have no higher risk for developing distal hypoperfusion, probably because they accounted for only one-third of our respondents. On the other hand, patients who had symptoms of distal ischemia were significantly older than those without this syndrome, which confirms old age as a factor that characterizes patients with DHIS [6,11] . Half of our respondents were smokers and this habit has been established as a significant feature in patients with pronounced symptoms of distal ischemia.…”
Section: Factors That Define Digital Hypoperfusion Ischemic Syndromementioning
confidence: 81%
“…A prerequisite for the occurrence of hand ischemia is reduced blood flow through the arterial system, excessive blood flow through distended blood vessels, inadequate vascular adaptation and reduced collateral perfusion. It is assumed that the incidence of ischemia could rise in the future due to popularization of vascular access in the proximal region of the elbow and the growing number of elderly people on dialysis [6,7] . The goal of this study was to determine clinical characteristics and survival parameters in patients with DHIS.…”
Section: Introductionmentioning
confidence: 99%
“…Some of its causes have been recognized in literature. Utilizing synthetic grafts;[2] old age patients, especially those with large bores graft access;[34] autogenous upper arm brachial-based AVFs in late chronic phase;[45] diabetes ground;[23] reduction in forearm arterial blood and bed pressure by high outflow exhaust through the graft or physically, turbulent flow at the arteriovenous anastomosis site;[678] side venous branches in AVFs;[8] severe peripheral arterial disease;[589] preoperative high digital-brachial index (DBI <0.45–1.0),[5610] and iatrogenic occurrence [11] are all previously known contributing factors for Steal development. The incidence of symptomatic Steal with hand ischemia ranges from 0.5% up to 28%.…”
Section: Discussionmentioning
confidence: 99%
“…ARHI tends to occur earlier relative to the index access for patients receiving an AVG. Scheltinga et al 25 reported from their systematic review that ARHI associated with AVGs tend to be acute, both in timing (< 24 hrs) and symptoms (i.e. acute ischemia), while that associated with AVFs tended to be more chronic (i.e.…”
Section: Discussionmentioning
confidence: 99%